Penyediaan Materi Sederhana Perguruan Tinggi Sebagai Solusi Untuk Masyarakat Yang Tidak Dapat Melanjutkan Pendidikan Ke Jenjang Perguruan Tinggi - Ade Mulyana (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2023)
This community service is focused on compiling and simplifying higher education materials to help increase competitiveness in this 4.0 industrial era. This research is motivated by the large number of high school graduates who cannot continue their studies at university with financial limitations. The objectives to be achieved in this Community Service (PKM) activity include: A). Create an online learning system or E-learning from the Pupilfirst.com Open Source Learning Management System (LMS) platform. B). Compile and simplify college materials. Because in this study, the process of making or designing the system was not made from scratch, the researchers only described the system design using a Mind Map and Use Case. The Matkul E-learning system was created with the Pupilfirst.com Learning Management System (LMS) platform, which is an Open Source LMS platform that focuses on online learning for students, and the researchers conducted testing using the testing method, namely Browser Compatibility. Keywords: E-learning, LMS (Learning Management System), Open Source, Browser Compatibility.